RURAL TOURISM THROUGH THE LENS OF INSTAGRAM USERS - Lazarević, Sonja; Stanišić, Tanja; Leković, Miljan; Pantić, Nemanja (Economics of Agriculture, 2025)
Rural tourism is a form of tourism that takes place in a rural environment and in which the tangible and intangible culture of the destination is experienced. Along with the growing interest of tourists in these elements, the attractiveness of rural tourism and its representation in Instagram posts is also increasing. The purpose of this research is to evaluate trends in rural tourism by analyzing Instagram images as a useful information base. The key methodological tool in research is image content analysis. The results of the research made it possible to draw conclusions about the most represented rural tourism destinations, key attractions and activities, gender specificities of participants in rural tourism, as well as its pronounced seasonality. In particular, the research led to the identification of education as an emerging activity in rural tourism. The research results can be useful for management organizations, rural communities, and tourism marketers. At the same time, the research emphasizes the usability of user-generated images on social media platforms in researching trends in the tourism market.